Epidemiology and the Italian national health service. Issue 6 (December 1995) - Vineis, P; Paci, E
Abstract : The Italian national health services is under criticism. Although recent legislative changes are intended to introduce managed competition, there is no clear epidemiological view of the health care needs and priorities. Several inconsistencies and inequalities (particularly between the northern and the southern regions) are obvious, both in the health status of the population and in the provision of health care. Problems that should be addressed by future governments are: the uneven distribution of medical technology; the persistence of large inequalities, documented by outcomes such as rheumatic fever, between northern and southern regions; the large variability in clinical practices; the lack of an explicit policy as far as the diffusion of advanced technology is concerned; the ensuing "hidden" rationing; and the peculiar relationship between public and private health structures. Both the current ideological shift towards a market economy for health care and the traditional lack of epidemiological input in health care planning could threaten a rational approach to these problems.